Using Surveys to Measure ’Value Added’ in Skills in Four Faculties - Grayson, J. Paul (Canadian Journal of Higher Education, 1999)
Some universities in Canada and other countries are interested in knowing the value-added to skills — e.g., critical and communication skills — by the university experience. The best way of obtaining information on this matter is through longitudinal analyses with appropriate control groups that utilize both subjective and objective measures of skills; unfortunately, such designs are costly and studies based on them take a long time to complete. In this article an alternate strategy that involved comparing the skills of entering and graduating students at York University is described. It is argued that information collected in this fashion can be of assistance in assessing the value added to specific skills and can be used in a diagnostic fashion by faculties concerned with skills development.